Lauching Geographic Education in to the 21st Century : The View from the United States. - Stoltman, Joseph; Wardley, C.; Kandi, Pavan (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1999)
Geographic education in the United States has experienced an unprecedented resurgence in the schools during the past two decades. There are several compelling reasons for a revival of the discipline, among them a thoroughly documented level of geographic illiteracy in the school age population that raised the ire of politicians, parents, and geographers alike (The Gallop Organization, 1988). This paper discusses the way that educational reform has addressed the problems facing geographic education on the eve of the new millennium. A successful approach to the issues necessitated being able to move geography education forward in three phases. They were: 1) awareness of the problems facing the discipline; 2) the development of rigorous content standards to guide geography education nationally, and 3) national and state assessments of student performance in geography and teacher preparation initiatives. The significance of each of the three phases is discussed within the context of geographic education within the United States.